The moral of the story: 'populism' and 'activism' in entrepreneurship. Issue 9 (20th October 2022) - Melin, Erik; Gaddefors, Johan; Ferguson, Richard
ABSTRACT: This paper engages with the concepts of 'populism' and 'activism' in entrepreneurial storytelling in order to explain how entrepreneurship may be both an individual and a collective endeavour. Through a case study of a moose park, we show how entrepreneurs move back and forth between individualism and collectivism with what seems to be little forethought. Our findings suggest that populism and activism function as a duality that essentially serves two purposes: populism reinforces the entrepreneur stereotype, highlighting the individual entrepreneur's business venture; whilst activism challenges stereotypes, initiating new meaning, and social and ecological value change. Embeddedness appears a necessary condition for both these processes – the social connections in context affect the possibilities to initiate change, whether individualist or collectivist. Thus, we contribute to entrepreneurship as practice by showing how storytelling both strengthens and changes social context; and how storytelling alters depending on the social context, and the different forms of embeddedness in it.